A COMPARATIVE STUDY OF ACHIEVEMENT MOTIVATION BETWEEN FOOTBALL AND HANDBALL PLAYERS (International Journal of Food and Nutritional Sciences, 2022)
For the present study, male players aged between 18 and 25 years who had participated at least at the state-level tournaments of Manipur were selected as subjects. The study adopted a descriptive comparative research design to examine and compare sports achievement motivation among football and handball players. A total of 60 players, including 30 football players and 30 handball players, were selected for the study. Sports achievement motivation was assessed using the standardized Sports Achievement Motivation Scale developed by Dr. P. S. Goregaonkar and Dr. R. D. Helode (2009).Data were collected through the administration of the questionnaire under standardized conditions after obtaining prior permission from the concerned clubs and institutions. The responses obtained were scored and systematically arranged for statistical analysis. An independent samples t-test was applied to determine the significance of differences between the two groups, with the level of significance set at 0.05. The results indicated a statistically significant difference in sports achievement motivation between football and handball players (t = 4.058, p< 0.05). Football players showed higher levels of sports achievement motivation than handball players. The findings support previous research and indicate that regular training and participation in football may positively contribute to the development of sports achievement motivation among male players.